'A dead letter of the statute book': the strange bureaucratic life of the Bihar Food Economy and Guest Control Order, 1950–1954. Issue 3 (2nd July 2016) - Kantor, Hayden S.
ABSTRACT: In the years following India's independence, food shortages threatened to destabilize the country. In response, the Indian Ministry of Food in 1950 introduced the Food Economy and Guest Control Order. This statute was designed to check waste by limiting the number of guests permitted at social gatherings and regulating the types of food items served. The Guest Control Order quickly became a flashpoint between the bureaucrats in Delhi who conceived of the austerity measures and their counterparts in state capitals tasked with implementing the policy. This article examines the correspondence between the Ministry of Food and the Bihar Supply and Price Control Department regarding the Guest Control Order for insight into early debates about the appropriate role of the state in the economy. The exchange reveals the conflicting priorities – e.g. national objectives versus local exigencies, social cohesion versus enforceability – that characterized state policy in the early years of independent India. In these debates, assumptions about Indian culture, in general, and food practices, in particular – e.g. what is good for citizens to eat, how these foods ought to be eaten – became contested in the lawmaking process and emerged as central to the process of early nation-making.